Management of Village-Owned Enterprises (BUMDes) - Puansah, Irman; Ritonga, Soritua; Efendi Pasaribu, Safran; Parapat, Natalia; Pulungan, Darmansyah; Syahrin, Elfi (KnE Social Sciences, 2023)
This research is motivated by the low ability of the Village Government in managing Village-Owned Enterprises (BUMDes). BUMDes, which is one of the institutions engaged in the social and economic sector as a service provider to the community, especially regarding the business sector, has not been able to have a big effect on society. BUMDes in Tambiski Nauli Village has not developed optimally and has not been able to provide benefits for the community and for the Village Government. This study aims to (i) analyze the management of BUMDes in Tambiski Nauli Village, Naga Juang District, Mandailing Natal Regency. (ii) To analyze the obstacles faced in the management of BUMDes in Tambiski Nauli Village. This research uses qualitative research methods, data collection methods are carried out by interviews and observation through field research. The results showed (i) the management of BUMDes in Tambiski Nauli Village was not optimal, the BUMDes that were formed had not had a major effect on improving the community’s economy. The management that is carried out is not yet structured and not well directed. The role of the Village Head who has a control function in management is not optimal. (ii) Obstacles faced in managing BUMDes include lack of creativity in developing BUMDes, weak management skills and weak coordination. Keywords: BUMDes; community’s economy; management skills